PENGEMBANGAN KONSEP DAN PEMBAHARUAN APLIKASI IZIN TINGGAL ONLINE DI KANTOR IMIGRASI KELAS I KHUSUS TPI NGURAH RAI - Anggrek, Denise Valeria; I Ketut Gede Suhartana; I Gede Surya Rahayuda (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2024)
This research aims to develop the concept and implement updates to the online residence permit application at Immigration Office Class I TPI Ngurah Rai. The study is conducted with the objective of enhancing efficiency and improving services for residence permit applicants. Data was collected through applicant satisfaction surveys and interviews with immigration officials and application developers. The analysis identified shortcomings in the existing application, such as a complex user interface and the lack of accurate status monitoring features. Based on these findings, a new development concept is proposed, focusing on interface improvements, faster document verification, and the addition of real-time status monitoring features. The implementation of these updates requires strengthening technology infrastructure, enhancing data security, and involving stakeholders. This research provides a significant contribution to the development of the online residence permit application at the Immigration Office Class I TPI Ngurah Rai, with the potential to enhance service efficiency and serve as inspiration for other immigration offices.